To what extent can a guided imagery intervention designed to enhance self-esteem help to reduce social exclusion in key stage 2? - Woodward, Sophie (2010)
The topics of self-esteem and social inclusion have been subject to much research in educational psychology, with positive correlation often being found to exist between the two. However, very little research has been conducted into the efficacy of guided imagery - a person-centred cognitive therapeutic technique – on enhancing either self-esteem or social inclusion, particularly in school-age populations. Identifying the gap in existing literature, this study therefore assessed the extent to which a five-session guided imagery intervention was associated with increases in both self-esteem (as measured by the Lawrence Self-Esteem Questionnaire; Lawrence, 1982) and social inclusion (as measured by the Social Inclusion Survey; Frederickson & Graham, 1999, and the Peer Problems and Prosocial Behaviour subscales of the Strengths and Difficulties Questionnaire; Goodman, 1997). This quantitative data was supplemented by a limited collection of qualitative questionnaire data, which was analysed using content analysis. Both forms of data were collected from 46 Year 4 and 5 pupils from three mainstream primary schools, who had been randomly allocated either to experimental groups or waiting list control groups. Qualitative data was also collected from the four members of school staff who had been trained in facilitating the intervention. Data analysis indicated that the guided imagery intervention had few salient effects on self-esteem or social inclusion as measured by the instruments used, but there was some qualitative evidence of increased self-esteem and social inclusion of participants in the experimental condition. The results of this study are discussed in the context of existing literature, and implications for future research and practice are explored.